FISHERIES OF VELLAR ESTUARY PORTO NOVO - Natarajan, P; Devadoss, P; Muniyandi, K (Indian Journal of Fisheries, 2011)
Results of a study of the fishery of fin fishes and shell fishes in the estuary of Vellar at Porto Novo (11Â° 29’ N; 79Â° 46’ E) for the period from December 1973 to Novemiber 1974 are reported. Several methods of fishing employed in this estuary are diiscussed. Among fin fishes, as a single group mullets (Mugil spp.) form the major fishery. The topography of the estuary, fluctuations of th6 fishery, and tb; major influence of land drainage due to rain during November and December on the fishery are also discussed. It is estimated that 1,70,000 kg. of fishes and orustacearis are landied annually. The clam wealth of Vellar is one of the best in Tamil Nadu and about 2,10,000 kg. of clams are estimated to be handpicked annually.